CANDYΓÇÖS BOWL: POLITIK KERUKUNAN BERAGAMA DI INDONESIA (Harmoni, 2013)
Politics Candy Bowl ΓÇÿs start from the assumption that the dispute is social fact that can not be avoided . Disputes will lead to destruction if all parties mutually develop destructive spirit , beat and kill each other . These consequences also can not be avoided and it would be worse if those entities become part of instrumentalization of interest, so thing suppose to be easily resolved become more difficult to be resolved due to the dominacy of the interests behind it. The politic of Agonism requires a plural social life like candy ΓÇÿs bowl where all the candy`s colors still exist, but they are in a protected space which guarantee the independence`s life of all elements without reduced by ideological values beyond them selves.
Keywords: Agonisme; Politik Kerukunan; Kekerasan